Updated Brazilian’s Georeferenced Soil Database – An Improvement for International Scientific Information Exchanging - Benedetti, Marcelo Muniz; Curi, Nilton; Sparovek, Gerd; Filho, Amaury de Carvalho; Silva, Sérgio Henrique Godinho (IntechOpen, 2011)
None